"The chip in a perfect piece of pottery": An ethnographic study of parents' online narratives when a child has cancer - Meridith Burles; Jill M.G. Bally (Elsevier, 2022)
In recent years, the Internet has increasingly been used to communicate about personal health, illness, and caregiving experiences. For instance, parents of children with cancer share personal accounts online describing their family experiences and emotions as they navigate childhood cancer. These online accounts offer insight into the nature of parents' experiences and narrative structures adopted to communicate and find meaning. Using a narrative methodology and virtual ethnographic methods grounded in interpretivist and constructivist principles, we examined 23 online accounts of varying lengths shared publicly by Canadian parents of children with cancer. Analysis focused on the content and structure of accounts, identifying common experiences and forms of narration. Three dominant narrative types emerged related to the Idealized Child, Faith, and Failure. To meaningfully convey commonalities across the sample and uphold confidentiality, a Fabrication approach (Markham, 2012) was adopted to develop composites representing the three narrative types, which illuminate family experiences and meaning-making processes. The findings can enhance understanding of family experiences of childhood cancer and inform psychosocial interventions that assist healthcare teams with supporting families of children with cancer more effectively.